2013
DOI: 10.1128/aac.02508-12
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Positive Nigerian Adults Harbor Significantly Higher Serum Lumefantrine Levels than HIV-Negative Individuals Seven Days after Treatment for Plasmodium falciparum Infection

Abstract: e Management of coinfection with malaria and HIV is a major challenge to public health in developing countries, and yet potential drug-drug interactions between antimalarial and antiviral regimens have not been adequately investigated in people with both infections. Each of the constituent components of artemether-lumefantrine, the first-line regimen for malaria treatment in Nigeria, and nevirapine, a major component of highly active antiretroviral therapy, are drugs metabolized by the cytochrome P450 3A4 isoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…influenced by CYP2B6 polymorphisms (14,20,36). The overall 30% higher exposure to lumefantrine when not stratified to CYP2B6 c.516GϾT genotypes is consistent with data from previous similar parallel design studies (29,(32)(33)(34). Kredo et al (29) recruited ART-naive patients as control and reported 56% significantly higher lumefantrine exposure.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…influenced by CYP2B6 polymorphisms (14,20,36). The overall 30% higher exposure to lumefantrine when not stratified to CYP2B6 c.516GϾT genotypes is consistent with data from previous similar parallel design studies (29,(32)(33)(34). Kredo et al (29) recruited ART-naive patients as control and reported 56% significantly higher lumefantrine exposure.…”
Section: Discussionsupporting
confidence: 83%
“…Kredo et al (29) recruited ART-naive patients as control and reported 56% significantly higher lumefantrine exposure. Chijioke-Nwauche et al (32) recruited HIV-negative subjects as controls and obtained 29% higher day 7 plasma lumefantrine levels versus the observed 37% rise in the present study's day 6 plasma lumefantrine levels (C day 6 ). The Maganda et al (33) study in HIV-and malaria-coinfected patients recruited ART naive patients as control and reported 25% nonsignificantly higher lumefantrine exposure compared to the 30% rise obtained in this study.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…(8)(9)(10)(11)(12) Results are inconsistent in the few studies on October 5, 2020 by guest http://aac.asm.org/ Downloaded from investigating the effect of nevirapine-based ART on lumefantrine exposure, showing increased, decreased or no effect on lumefantrine exposure. (13)(14)(15)(16)(17)(18) Dolutegravir-based ART is being rapidly adopted as first-line HIV treatment; Dolutegravir is an HIV-integrase inhibitor reported to have minimal effects on CYP3A4 and a study has shown that DTGbased ART did not alter lumefantrine exposure significantly. (19,20) Additionally, no information is available on whether malaria or HIV disease may affect lumefantrine pharmacokinetics.…”
Section: Main Text (4116 Words) Introductionmentioning
confidence: 99%
“…Etravirine decreased lumefantrine AUC by 13%. [28] Unexpectedly, nevirapine was found to significantly increase exposure to lumefantrine in some studies, [31, 35, 38, 39]…”
Section: Resultsmentioning
confidence: 99%